Semi-collusive advertising and pricing in experimental duopolies - Andreas Nicklisch (Max Planck Institute for Research on Collective Goods, 2008)
This article tests experimentally whether a high degree of collusion on advertisement expenditures facilitate tacit price collusion in duopoly markets. Two environments are tested, in which the size of the spillover between advertising expenditures is varied. The results show that the competitiveness of advertising and prices are significantly higher when the advertising spillover is higher than the price spillover than when advertising spillover is lower than the price spillover. In the second environment, a higher degree of advertising collusion leads for experienced players to a higher degree of price collusion. In the first environment, players behave at most semi-collusively, that is, if at all, they collude on advertising, but compete over prices.
Keywords: D43; L13; M37; 330; Advertising; duopoly competition; experimental economics; price collusion; semi-collusive markets; Werbung; Spillover-Effekt; Betriebliche Preispolitik; Wettbewerbsbeschränkung; Duopol; Theorie